The Imagined Cities of Three Canadian Painters - Caulfield, Jon (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1991)
The paper argues that cityscapes of Toronto painted by John Gillespie in 1844/5, Robert Gagen in 1914 and Christiane Pflug in 1968-71 each illuminate and are illuminated by the urban historical periods in which they were created. The paper's conclusion suggests that three frameworks for looking at painters' images of cityscape are those of political economy, "sentiment and symbolism", and "discursive" relationship of observer and object.